Graphene in wearable textile sensor devices for healthcare. Issue 3 (3rd July 2022) - Ahmed, Md Raju; Newby, Samantha; Mirihanage, Wajira; Potluri, Prasad; Fernando, Anura
Abstract: Current advances in flexible, textile wearable device manufacturing are being made through a new generation of materials and nanotechnology. These recent advances make integrating functional sensors into textiles easier and allow for widespread application, including healthcare. Through improving the materials and integration techniques used, wearable sensors can be used to create personalised healthcare products that can monitor vital physical and biological signals. One material that is leading the way for future healthcare systems is graphene. Graphene has superior electrical and thermal conductivity, high chemical stability, and extreme mechanical properties. It also offers a variety of hybrid types that are useful when designing cost-effective and scalable electronic devices for textile applications. This review will outline how graphene and textile-based materials are being used to manufacture wearable health-monitoring devices as well as the challenges and opportunities of graphene and textile-based materials.